2016
DOI: 10.1530/erc-16-0171
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations with neuroendocrine tumor risk: results from a genome-wide association study

Abstract: The etiology of neuroendocrine tumors remains poorly defined. Although neuroendocrine tumors are in some cases associated with inherited genetic syndromes, such syndromes are rare. The majority of neuroendocrine tumors are thought to be sporadic. We performed a genome-wide association study (GWAS) to identify potential genetic risk factors for sporadic neuroendocrine tumors. Using germline DNA from blood specimens, we genotyped 909,622 SNPs using the Affymetrix 6.0 GeneChip, in a cohort comprising 832 neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…It is unlikely, however, that celiac disease is a significant risk factor in Blacks given its low incidence in this population [55,56]. For small bowel neuroendocrine tumors, GWAS evaluations have identified risk variants upstream of ELK3 , though the impact of these variants by race is not known [57]. Additional risks for neuroendocrine tumors include family history, BMI, diabetes and tobacco [58].…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely, however, that celiac disease is a significant risk factor in Blacks given its low incidence in this population [55,56]. For small bowel neuroendocrine tumors, GWAS evaluations have identified risk variants upstream of ELK3 , though the impact of these variants by race is not known [57]. Additional risks for neuroendocrine tumors include family history, BMI, diabetes and tobacco [58].…”
Section: Introductionmentioning
confidence: 99%
“…No other candidate gene mutations were identified in the other families. Subsequent studies have also not identified this IPMK mutation as a driving mutation in other familial SBNET candidate families (7,17,33).…”
Section: Familial Sbnetmentioning
confidence: 99%
“…Another large genome wide association study was performed looking at 293 sporadic SBNET. Three associated single nucleotide polymorphisms were identified on chromosome 12 just upstream of ELK3 , a transcription factor associated with angiogenesis ( 17 ). Earlier studies also identified APC and SRC mutations in 23 and 25% of SBNET although these have not been confirmed in more recent studies ( 14 , 18 ).…”
Section: Molecular Characteristics Of Sporadic and Familial Small Bowmentioning
confidence: 99%
See 1 more Smart Citation
“…No LOH of MUTYH was reported in the I-NET samples. Additional studies on SNP associations to I-NETs have focused on spontaneous and not familial I-NETs [106,107].…”
Section: Epidemiological Studiesmentioning
confidence: 99%